Rationalisations for women-only randomised controlled trials in conditions that affect both sexes: a scoping review protocol. Issue 2 (16th February 2021) - Matthewson, Ainsley; Bereznyakova, Olena; Dewar, Brian; Davis, Alexandra; Fedyk, Mark; Yogendrakumar, Vignan; Fergusson, Dean A; Gocan, Sophia; Dowlatshahi, Dar; Fahed, Robert; Shamy, Michel
Abstract : Introduction: Women have historically been under-represented in randomised controlled trials (RCTs), including many landmark RCTs that established standards of care. In light of this fact, some modern researchers are calling for replication of earlier landmark trials with women only. This approach is ethically concerning, in that it would require some enrolled women to be deprived of treatments that are currently considered standard of care. Objective: In an attempt to better understand the justification of a women-only approach to designing clinical trials, this study looks to systematically categorise the number of women-only RCTs for conditions that affect both men and women and the reasons given within the medical and philosophical literatures to perform them. Methodology: This scoping review of the literature will search, screen and select articles based on predetermined inclusion/exclusion criteria, after which a grounded theory approach will be used to synthesise the data. It is expected that there will be a variety of reasons given for why a women-only trial may be justified. Electronic databases that will be searched include MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, Cochrane Clinical Trials Register, Web of Science Proceedings, ClinicalTrials.gov, Philosopher's Index, Phil Papers, JSTOR, Periodicals Archive Online, Project MUSE and the National Reference Centre for Bioethics. Significance: The scope of this study is to determine published rationales used to justify women-only randomised trials, both in the case of new trials and in the repetition of landmark trials. Ethics and dissemination: Research ethics board approval is not required for this study as there is no participant involvement. Results will be published as a stand-alone manuscript and will inform a larger project related to the ethics of a women-only RCT of carotid intervention for women with symptomatic high-grade carotid stenosis.